2017
DOI: 10.1186/s13018-016-0506-7
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided percutaneous peripheral nerve stimulation for analgesia following total knee arthroplasty: a prospective feasibility study

Abstract: BackgroundPeripheral nerve stimulation has been used for decades to treat chronic pain but has not been used for postoperative analgesia due to multiple limitations, beginning with invasive electrode placement. With the development of small-diameter/gauge leads enabling percutaneous insertion, ultrasound guidance for accurate introduction, and stimulators small enough to be adhered to the skin, neurostimulation may now be provided in a similar manner to continuous peripheral nerve blocks. Here, we report on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
92
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 47 publications
5
92
0
1
Order By: Relevance
“…Previous investigations involving the same helically coiled lead used in the current study have reported a 7.5% average incidence of fracture deep to the skin during removal (none occurred in the subjects of the current study) . All previous lead remnants have been left in situ with no negative sequelae reported in up to a one year period of assessment . Importantly, magnetic resonance imaging may be performed safely in patients with retained lead fragments at 1.5 Tesla .…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Previous investigations involving the same helically coiled lead used in the current study have reported a 7.5% average incidence of fracture deep to the skin during removal (none occurred in the subjects of the current study) . All previous lead remnants have been left in situ with no negative sequelae reported in up to a one year period of assessment . Importantly, magnetic resonance imaging may be performed safely in patients with retained lead fragments at 1.5 Tesla .…”
Section: Discussionsupporting
confidence: 49%
“…One lead of the current investigation broke exterior to the subject where the lead met the connection block, which has not yet been reported . Previous investigations involving the same helically coiled lead used in the current study have reported a 7.5% average incidence of fracture deep to the skin during removal (none occurred in the subjects of the current study) .…”
Section: Discussionmentioning
confidence: 79%
“…Accordingly, the medical professional should inform the patient regarding these matters and make a notation in the patient's medical records. It should be noted that the rate of lead fracture (as determined by visual inspection of the removed lead) associated with lead removal has been reported to be 7.5% . Notably, there were no reports of infectious or neurologic complications related to the presence of lead fragments in situ , nor any reports of indwelling leads fracturing during therapy .…”
Section: Discussionmentioning
confidence: 98%
“…No serious device‐related adverse events have occurred across all studies and, for the adverse events that did occur, these required little or no medical treatment . In addition, there have been no reports of induced sensory, motor, or proprioception deficits during use of this unique means of applying PNS, thus, enabling percutaneous PNS to be utilized during physical rehabilitation (e.g., during the immediate postoperative period) and activities of daily living .…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] In 2 of these abstracts, 32,33 a total of 10 individuals were included who experienced postoperative knee pain difficult to control with oral analgesics between 6 and 97 days after surgery. Using ultrasound guidance, a femoral and/or sciatic nerve electrical lead was inserted, depending on where most of the pain originated (anterior vs posterior).…”
Section: Application To Postoperative Painmentioning
confidence: 99%